Recent Advancements in Polymer-Based Composite Electrolytes for Rechargeable Lithium Batteries - Tan, Shuang-Jie; Zeng, Xian-Xiang; Ma, Qiang; Wu, Xiong-Wei; Guo, Yu-Guo (Electrochemical energy reviews, 2018)
In recent years, lithium batteries using conventional organic liquid electrolytes have been found to possess a series of safety concerns. Because of this, solid polymer electrolytes, benefiting from shape versatility, flexibility, low-weight and low processing costs, are being investigated as promising candidates to replace currently available organic liquid electrolytes in lithium batteries. However, the inferior ion diffusion and poor mechanical performance of these promising solid polymer electrolytes remain a challenge. To resolve these challenges and improve overall comprehensive performance, polymers are being coordinated with other components, including liquid electrolytes, polymers and inorganic fillers, to form polymer-based composite electrolytes. In this review, recent advancements in polymer-based composite electrolytes including polymer/liquid hybrid electrolytes, polymer/polymer coordinating electrolytes and polymer/inorganic composite electrolytes are reviewed; exploring the benefits, synergistic mechanisms, design methods, and developments and outlooks for each individual composite strategy. This review will also provide discussions aimed toward presenting perspectives for the strategic design of polymer-based composite electrolytes as well as building a foundation for the future research and development of high-performance solid polymer electrolytes. Graphical Abstract